ESTHETIC ASSESSMENT OF LANDSCAPES AND ITS FEATURES (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
The article presents two methods for assessing the aesthetic properties of landscapes: by photography and by method of calculation. These methods can be used for various purposes.
Keywords: Northern Armenia; recreation; evaluation; tourism